Environmental Regulation in the 1990s: God, Mill and the Fuchsia Car - King, Angus (Maine Policy Review, 1992)
Angus King has found himself on both sides of the environmental regulation fence, as he notes in this address, which he delivered at the PURE ’92 Conference. Here, he offers eleven observations about the state of environmental regulation in the 1990s. An attorney, King is the president of Northeast Energy Management, Inc., which develops large-scale electrical energy conservation projects at commercial and industrial facilities.